Influence of fertilization on growth and yield of onion under semi-arid conditions. Issue 4 (4th July 2022) - Mrema, Emmanuel; Mtunda, Kiddo; Mbise, Victor
ABSTRACT: Potential yield of onion ( Allium cepa L.) in semi-arid regions is reduced by abiotic (soil infertility, poor agronomic practices, and unbalanced fertilization) and biotic (use of low yielding varieties, insect pest, and diseases) challenges. Soil infertility causes up to 60% yield loss in onion. This study was undertaken to assess the influence of manure and phosphorus (P2 O5 ) fertilizer levels on growth and bulb development of onion under semi-arid conditions. Manure at 30 or 60 kg/5 m 2 or 0.24, 0.48 or 0.62 g/plant for phosphorus and treatments combined at each application rate were used. Application of phosphorus and manure at 0.24 to 0.48 g/plant and 30 kg/5 m 2 plot, respectively, improved vegetative and bulb development and weight. A combination of 30 kg/5 plot manure and 0.48 g/plant phosphorus produced an economic benefit based on number and weight of marketable bulbs. Application of 0.24 to 0.31 t∙ha −1 of P2 O5, increased number of unmarketable bulbs. 'Red Bombay' performed better than 'Red Mantle.' Individual or combination application of P2 O5 at 0.12 to 0.31 t∙ha −1 and organic manure at 60 t∙ha −1 may produce adequate yield, and 'Red Bombay' maybe a better choice than 'Red Mantle' under semi-arid conditions. Application of manure and phosphorus improves vegetative and yield in onion cultivars. Use of 30 kg/5 m 2 of manure and a combination of 30 kg/5 m 2 and 0.48 g/plant manure and P2 O5, respectively, appear to improve yield.